Bornavirus Encephalitis Shows a Characteristic Magnetic Resonance Phenotype in Humans. Issue 4 (29th August 2020) - Finck, Tom; Liesche‐Starnecker, Friederike; Probst, Monika; Bette, Stefanie; Ruf, Viktoria; Wendl, Christina; Dorn, Franziska; Angstwurm, Klemens; Schlegel, Jürgen; Zimmer, Claus; Wiestler, Benedikt; Wiesinger, Isabel; et al.
Abstract : Objective: The number of diagnosed fatal encephalitis cases in humans caused by the classical Borna disease virus (BoDV‐1) has been increasing, ever since it was proved that BoDV‐1 can cause human infections. However, awareness of this entity is low, and a specific imaging pattern has not yet been identified. We therefore provide the first comprehensive description of the morphology of human BoDV‐1 encephalitis, with histopathological verification of imaging abnormalities. Methods: In an institutional review board‐approved multicenter study, we carried out a retrospective analysis of 55 magnetic resonance imaging (MRI) examinations of 19 patients with confirmed BoDV‐1 encephalitis. Fifty brain regions were analyzed systematically (T1w, T2w, T2*w, T1w + Gd, and DWI), in order to discern a specific pattern of inflammation. Histopathological analysis of 25 locations in one patient served as correlation for MRI abnormalities. Results: Baseline imaging, acquired at a mean of 11 ± 10 days after symptom onset, in addition to follow‐up scans of 16 patients, revealed characteristic T2 hyperintensities with a predilection for the head of the caudate nucleus, insula, and cortical spread to the limbic system, whereas the occipital lobes and cerebellar hemispheres were unaffected. This gradient was confirmed by histology. Nine patients (47.4%) developed T1 hyperintensities of the basal ganglia, corresponding to accumulated lipid phagocytes on histology and typical for late‐stage necrosis. Interpretation: BoDV‐1 encephalitis shows a distinct pattern of inflammation in both the early and late stages of the disease. Its appearance can mimic sporadic Creutzfeldt–Jakob disease on MRI and should be considered a differential diagnosis in the case of atypical clinical presentation. ANN NEUROL 2020;88:723–735